Minding the gap: investigating the alignment of information organization research and practice, - White, Hollie; Hider, Philip; Jamali, Hamad (Information Research, 2019)
Introduction. The issues that practitioners want researched and those that are studied by researchers are often considered not to align very well. This paper investigates the extent to which a gap between research and practice exists in the field of information or knowledge organization, using a novel index of topical overlap between research and practice discourses. Method. The degree of alignment was measured by comparing samples of research-oriented and practice-oriented discourse published between 2013 and 2017. Information organization research was represented by scholarly articles, Information organization practice by professional blogs, webinars and conferences. Analysis. The texts were analysed using software which identified the most frequently used terms; the number of top terms, following deletion of generic terms and normalisation, that overlapped between corpora constituted the index of topical overlap. Results. The number of overlapping terms between information organization research and practice corpora was about halfway between the number of overlapping terms between highly similar and unrelated corpora. Conclusions. The results suggest a fair degree of alignment between information organization research and practice. The index used needs further testing, but appears to be a promising, unobtrusive tool for comparing the degree of alignment between research and practice in different fields.